Otolith shape analysis of Decapterus smithvaniza from Sibuyan and Sulu seas, Philippines. - Murata, Elyssa Marie M. (2023)
A comparative analysis was conducted to assess the differences in the otoliths of Decapterus smithvanizi specimens collected from Sibuyan and Sulu Seas, located in the Philippines. The methodology employed in this study encompassed various technique for shape analysis. These techniques involved identifying and extracting the outline otoliths, generating Wavelet and Fourier coefficients, measuring otolith dimensions such length, width, area, and perimeter, and evaluating the Wavelet coefficients as shape descriptors using statistical tests such as Analysis of Variances (ANOVA), Shapiro-Wilk normality, and Mann-Whitney U test. During the initial analysis, the assessment of the left and right otoliths, along with the comparison of the right otoliths among male and female D. smithvanizi specimens, did not show any statistically significant differences. Therefore. It was hypothesized that the otoliths sample, irrespective of their laterality (left or right) or the sex (male and female) of the D. smithvanizi specimens from which they were extracted, could be utilized as a method for comparing the two neighboring fishing grounds, namely the Sibuyan and Sulu Sea. Furthermore, the statistical analysis revealed a notable difference (p<0.05) between the samples of D. smithvanizi collected from two fishing grounds. This suggest that D. smithvanizi from the Sibuyan Sea was a separate phenotypic stock from those of the Sulu Sea. In addition, it is imperative to incorporate studies on otolith morphology and morphometry in order to evaluate the distinct characteristics that differentiate the two stocks from one another, as well as the implications of these descriptors for the fish samples.
Thesis (Undergraduate, Bachelor of Science in Fisheries) College of Fisheries and Ocean Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2023.
Keywords: Decapterus smithvaniza -- Sibuyan sea , Philippines; Decapterus smithvaniza -- Sulu sea, Philippines